Development and agitating the job of the great kazakh thinker and philosopher Abay in china. - Sharypkazy., N. (Journal of Oriental Studies, 2016)
Development and agitating the job of the great Kazakh thinker and philosopher Abay in China, translating aforecited job into Chinese and Uigur languages, achieve them to newspaper and journals can be divided into several phase. For Kazakh people, who live in China, Abay is their poet, their man and they imagine him like vertex of the highest mountain and proud of him among Chinese and Uigur people.